Liquidity Risk Exposure and its Determinants in the Banking Sector: A Comparative Analysis between Islamic, Conventional and Hybrid Banks - Mohammad, Sabri; Asutay, Mehmet; Dixon, Rob; Platonova, Elena (Journal of International Financial Markets, Institutions and Money, 2020)
This study aims to explore and examine the liquidity risk that Islamic banks are exposed to in a comparison with conventional and hybrid banks in the case of 145 commercial banks for the period of 1996–2015. This study also examines the factors determining the liquidity risk exposure of the sampled banks by employing a panel data regression model with the random effect technique by considering bank specification, macroeconomy, governance and ownership-related variables. The findings for the sampled banks demonstrate that Islamic banks are more exposed to liquidity risk than conventional and hybrid banks. In addition, the results show that the stringency of capital regulations and credit risk have a negative and significant impact on liquidity risk. Moreover, the results demonstrate that liquid assets and long-term debts are positively associated with liquidity risk exposure. While the empirical results show that long-term debt significantly affects liquidity risk, the results indicate an insignificant impact of liquid assets on the liquidity risk exposure of the sampled banks. The results also depict that bank size, governance and ownership concentration as well as GDP are important control variables in reducing the liquidity risk exposure of Islamic banks.
EPrint Processing Status: Full text deposited in DRO